THE PRACTICE OF POLITICAL IDENTITY: A SYSTEMATIC REVIEW - Iradhad Taqwa Sihidi; Dedik Fitrah Suhermanto; Salahudin Salahudin; Muhammad Kamil; Ach. Apriyanto Romadhan (JWP (Jurnal Wacana Politik), 2022)
This study aims to conduct a bibliometric analysis of the theme of political identity. This topic has recently become a center of attention and the strengthening of right-wing populism, for example, has succeeded in giving victory to several leaders such as Donald Trump, Josh Bolzonaro, and Duterte. Using the Scopus database from 2016 through 2021, concept mapping and clustering related to the theme of political identity will be seen. Data was collected through searching the Scopus database with the keyword political identity which resulted in 520 related articles. The data analysis focused on cluster analysis, dominant topics, related themes, and mapping of political identity study topics, based on the number of articles visualized and analyzed using VOSviewer and WordStat 8 software. This research shows that the study of political identity has four dominant keywords that often appear, namely: Political Identity, identity, Politics, and Political Ideology. This means that these four topics are the main focus of attention written by most authors. This shows that the topic of politics is very closely related to its use as a basis for one’s politics and will become a big challenge for democracy in the future.